Visible light induced electron transfer behavior of a CeO2-loaded HfO2/carbon cluster nanocomposite material - Matsui, Hideo; Nishii, M.; Karuppuchamy, Subbian; Jeong, Jae Mun; Hassan, Mohd Ali; Yoshihara, Masakuni (Elsevier, 2012)
The microwave-irradiated calcination of HfOCl2/starch complex I under an air atmosphere produced the HfO2/carbon cluster composite material which is denoted as Ic. The obtained composite material could decompose methylene blue under the irradiation of light (λ > 460 nm). The surface of Ic was loaded with CeO2 particles to obtain CeO2-loaded composite material, which can decompose the aqueous silver nitrate solution and produce O2 and Ag in the ratio of 1:4.2. Water photo-decomposition experiment was also carried out using Pt-modified composite materials.